Incidencia de las políticas públicas en el desarrollo sostenible del turismo en la provincia de Trujillo para el período 2010 - 2015 - Matta Ulloa, Angie Mariene (2017)
The purpose of this research is to demonstrate whether during the years 2010 to 2015 the public policies of the tourism sector, explained through the variables: investment in tourism development and investment in tourism education, has had an impact on the sustainable development of tourism in the province of Trujillo, explained through the variables: demand of the internal tourism, demand of receptive tourism and level of employment generated by the tourism sector. Regarding to the public policies of the tourism sector employed during the study period, they are contained in the PENTUR 2008 - 2018 and in PENTUR 2012-2021 and its importance for the good development of this sector, since they are the guidelines on which the Sub-Management of tourism of the Provincial Municipality of Trujillo work in order to achieve a sustainable and competitive development of the tourist activity. For the development of the present investigation, quantitative information has been used, related to the statistical information existing in the different units of the national, regional and local government related to the tourism sector, as well as qualitative information related to the evolution of this sector in the province of Trujillo for the study period. The research emphasizes the importance that the public policies of the tourism sector have to achieve the sustainable development of this sector; but without adequate monitoring and evaluation the objectives for which they were raised can not be achieved, as in the case of the province of Trujillo, where it has been concluded that public policies in the tourism sector have not significantly affected sustainable development of this sector for the period 2010-2015; In addition, it has been determined that since the province of Trujillo is a destination that contains a great variety of tourist attractions, it is not exploited in its entire dimension due to the lack of leadership and management of the authorities, as well as social problems such as crime and informality.